High-Resolution Ultrasound Spectroscopy for the Determination of Phospholipid Transitions in Liposomal Dispersions - Diego Romano Perinelli; Marco Cespi; Giovanni Filippo Palmieri; Annalisa Aluigi; Giulia Bonacucina (MDPI AG, 2022)
High-resolution ultrasound spectroscopy (HR-US) is a spectroscopic technique using ultrasound waves at high frequencies to investigate the structural properties of dispersed materials. This technique is able to monitor the variation of ultrasound parameters (sound speed and attenuation) due to the interaction of ultrasound waves with samples as a function of temperature and concentration. Despite being employed for the characterization of several colloidal systems, there is a lack in the literature regarding the comparison between the potential of HR-US for the determination of phospholipid thermal transitions and that of other common techniques both for loaded or unloaded liposomes. Thermal transitions of liposomes composed of pure phospholipids (dimyristoylphosphatidylcholine, DMPC; dipalmitoylphosphatidylcholine, DPPC and distearoylphosphatidylcholine, DSPC), cholesterol and their mixtures were investigated by HR-US in comparison to the most commonly employed microcalorimetry (mDSC) and dynamic light scattering (DLS). Moreover, tramadol hydrochloride, caffeine or miconazole nitrate as model drugs were loaded in DPPC liposomes to study the effect of their incorporation on thermal properties of a phospholipid bilayer. HR-US provided the determination of phospholipid sol-gel transition temperatures from both attenuation and sound speed that are comparable to those calculated by mDSC and DLS techniques for all analysed liposomal dispersions, both loaded and unloaded. Therefore, HR-US is proposed here as an alternative technique to determine the transition temperature of phospholipid membrane in liposomes.